PENGARUH FINANCIAL DISTRESS TERHADAP FINANCIAL STATEMENT FRAUD YANG DIMODERASI OLEH CORPORATE GOVERNANCE - Ana Mardiana (Contemporary Journal on Business and Accounting, 2021)
Purpose – This research aims to examine the effect of financial distress on the financial statement fraud which is moderated by corporate governance. Design/methodology/approach – This study uses multiple regression analysis methods. Findings – The results of this study indicate that financial distress has a significantly positive effect on financial statement fraud. As well as the influence of the moderating interaction of corporate governance, it has a significant negative effect on the relationship between financial distress and financial statement fraud. Originality – The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019. Keywords: Financial Distress, Corporate Governance, Financial Statement Fraud Paper Type Research Result